2020
DOI: 10.1001/jamaneurol.2019.4476
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Spreading Depolarizations in Patients With Severe Traumatic Brain Injury

Abstract: IMPORTANCE Advances in treatment of traumatic brain injury are hindered by the inability to monitor pathological mechanisms in individual patients for targeted neuroprotective treatment. Spreading depolarizations, a mechanism of lesion development in animal models, are a novel candidate for clinical monitoring in patients with brain trauma who need surgery.OBJECTIVE To test the null hypothesis that spreading depolarizations are not associated with worse neurologic outcomes. DESIGN, SETTING, AND PARTICIPANTSThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 47 publications
2
84
0
Order By: Relevance
“…This disease not only affects individuals and families but also causes a burden to economies at a societal level (Mollayeva et al, 2018). Unfortunately, dozens of clinical trials have failed to improve the outcomes of TBI, mainly resulting from the monotherapies (Kline et al, 2016;Hartings et al, 2019). TBI is heterogeneous and dynamic with various secondary injury mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This disease not only affects individuals and families but also causes a burden to economies at a societal level (Mollayeva et al, 2018). Unfortunately, dozens of clinical trials have failed to improve the outcomes of TBI, mainly resulting from the monotherapies (Kline et al, 2016;Hartings et al, 2019). TBI is heterogeneous and dynamic with various secondary injury mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical data strongly support efficacy in terms of frequency of spreading depolarization (SD) as well as recovery from electrocorticography depression. This is fundamental as SD has been suggested as an important mechanism for secondary brain injury and delayed cerebral ischemia [22][23][24]. Ketamine also causes pulmonary vasodilation and bronchodilation [16][17][18], and both mean arterial pressure and heart rate increase.…”
Section: Which Are the Systemic Effects Of Ketamine?mentioning
confidence: 99%
“…22,23 This electrochemical and neurovascular imbalance explains the frequently observed differences in clinical presentation of lesional CSD symptomatology versus the more benign nonlesional CSD, such as that observed in migraine aura. 24 The incidence of CSD has been reported to be as high as 60% in TBI, 80% in SAH, and over 90% in aggressive strokes. 14 A recent animal study revealed that the presence of CSD correlated with concussive symptomatology post-mild TBI and a higher number of apoptic cells.…”
Section: Cortical Spreading Depolarizationmentioning
confidence: 99%